Bioinformatic analysis of Streptococcus uberis genes and genomes - Hossain, Muhammad Maqsud (2016)
Streptococcus uberis is a Gram-positive, catalase-negative member of the family Streptococcaceae and is an important environmental pathogen primarily responsible for a significant amount of bovine intramammary infections. This thesis describes the sequencing and comparison of multiple strains from clinical and sub-clinical infections. Following de novo assembly, these are compared to the single reference strain (0140J).